Effects of Supplementing Laying Hens with Purified Amino Acid Prepared from Animal Blood - N. Joshi; T. G. Wandita; S. Yang; H. Park; S. G. Hwang (Tropical Animal Science Journal, 2019)
The objective of the experiment was to investigate the effects of supplementing laying hens with purified amino acids (PAA) derived from the blood of animal slaughter house on their egg production, egg quality, and immune response. The experiment was based on completely randomized design. A total of 144 Isa Brown laying hens (56-weeks old) were randomly allotted to 4 treatments with 4 pen replications (control, T1: 0.05%, T2: 0.1%, and T3: 0.5% PAA). Each pen housed nine laying hens. The laying hens were reared under a deep litter system. Once a week, a total of 12 eggs of each treatment were collected for egg quality analysis. At the end of the experiment, blood samples were collected for biochemical analysis and cytokines profiles using ELISA kit assays. Hen day egg production and hen house egg production increased significantly (P<0.05) along with the increase in PAA supplementation. The average egg weight increased significantly (P<0.05) with PAA supplementation. Significant differences (P<0.05) were also found in egg shell strength, shell thickness, and albumen ratio. Blood biochemical variables, such as glucose, total cholesterol, blood urea nitrogen (BUN), total bilirubin, and glutamate oxalate transaminase (GOT) were within the normal range. However, the glucose was highest in the control group. Whereas, the total cholesterol and total bilirubin were highest in T2 as compared to control group. Plasma immunoglobulin A (IgA) and immunoglobulin G (IgG), interleukin-1 (IL-1), interleukin-2 (IL-2) concentrations were not affected by PAA supplementation. Plasma interferon gamma (IFNγ) of PAA supplemented treatment groups was significantly (P<0.05) lower than the control group. However, tumor necrosis factor alpha (TNFα) was significantly (P<0.05) higher in T2. On the basis of these results, we conclude that PAA supplementation improved the production performance of laying hens without affecting their health.